2022
DOI: 10.1080/21645515.2022.2119766
|View full text |Cite
|
Sign up to set email alerts
|

Current status of coronavirus disease 2019 vaccine research based on bibliometric analysis

Abstract: Vaccination is considered the most effective way to reduce the impact of coronavirus disease 2019 (COVID-19). Several new vaccines have been manufactured. This study aimed to assess the current status and prospects of COVID-19 vaccine research using a bibliometric analysis. We analyzed 3,954 scientific articles on COVID-19 vaccines in the Web of Science Core Collection (WoSCC). CiteSpace and VOSviewer were used for bibliometric visualization. Original articles and reviews were used for the analysis. A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In summary, these observations are in line with published findings regarding the diminishing power of un-adapted SARS-CoV-2-vaccinations to protect against immune escape variants of the virus that have accumulated mutations in the S1/-receptor binding domain [ 12 , 13 , 19 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In summary, these observations are in line with published findings regarding the diminishing power of un-adapted SARS-CoV-2-vaccinations to protect against immune escape variants of the virus that have accumulated mutations in the S1/-receptor binding domain [ 12 , 13 , 19 ].…”
Section: Discussionsupporting
confidence: 89%
“…By now, health care deals with the outcome of a heterogeneous vaccination regimen and continuous asynchronous endemic re-infection by various SARS-CoV-2 mutants. As a consequence, immune responsiveness to SARS-CoV-2 exhibits considerable variability within the population [ 9 ], and individualization of vaccination has become an issue in several countries [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from no specific research on the 2019‐nCoV variant of the coronavirus, a stream of publications was quickly produced at the epidemic onset, mainly consisting of reviews and editorials presenting expert opinions and perspectives based on knowledge of similar viruses and pandemics 12–15 . Early pleas for the vital importance of conducting and sharing empirical COVID‐19 research 16–18 were soon answered with a deluge of publications in the second half of 2020 19–22 . The relatively sparse data contained in early observations were supplanted with an expanding collection of data from more and larger‐scale studies, disseminated and cited at unprecedented rates.…”
Section: Introductionmentioning
confidence: 99%
“…A few bibliometric studies have been published on assessment of global COVID-19 vaccines literature, which make the quantitative and qualitative assessment by way of analyzing various features of research output and citations. [7][8][9][23][24][25][26][27][28][29][30] With the rapid growth COVID-19 vaccines literature, it was difficult to go through such large number of publications appearing in various databases. It is observed that there has been a non-availability of any bibliometric study on HCPs papers on COVID-19 vaccine and any not study providing a quick, comprehensive synthesis of relevant information on the related scientific orientations, gaps, collaborations, themes, or dynamisms on COVID-19 vaccines.…”
Section: Introductionmentioning
confidence: 99%